Microstructural validation of processing maps using the hot extrusion of P/M Nimonic AP-1 superalloy - Somani M.C.; Birla N.C.; Prasad Y.V.R.K.; Singh V. (My University, 2025)
The microstructural features of hot-extruded Nimonic AP-1 superalloy powder are presented in this paper. Experiments have been designed to validate the processing maps of Nimonic AP-1 microstructurally using a commercial extrusion process. The time average mean strain rate εt, has been used as the basis for selection of the extrusion parameter viz., ram speed and extrusion ratio. Extrusion was conducted under non-isothermal conditions. The microstructural evaluation of the material extruded in the dynamic recrystallization (DRX) domain of the processing map exhibited homogeneous deformation and a recrystallized structure, free from cracks and shear bands. Adiabatic shear bands and inter-crystalline cracks seen in the microstructures of other extruded products have been correlated accurately with the instability and cracking regimes of the processing map. © 1995.